Meningkatkan Nilai Ekonomi Lokal melalui Keripik Ubi Jalar yang Inovatif - Amelia Oktrivina Siregar; Indah Masri; Iha Haryani Hatta; Yuana Rizky Octaviani Mandagie; Mulyadi Mulyadi; Cotoro Mukri (LPMP Imperium, 2024)
Sweet potatoes are a key agricultural product in Indonesia, particularly in five significant provinces: West Java, Central Java, East Java, Irian Jaya, and North Sumatra. One popular way to prepare sweet potatoes is by making them into delicious and nutritious chips. Chips are dry, crunchy snacks known for their durability, convenience, and ease of storage. Creating sweet potato chips could boost the economic value of fresh sweet potatoes. Given these points, introducing innovative sweet potato chips with enhanced nutritional value presents an enticing solution to address community nutritional needs and create new snack options. With a shortage of processed sweet potato products available, offering a variety of sweet potato chip flavors can also promote public health.